Canine epilepsy/seizure occurrence in primary care and referral populations: a look into the epidemiology across countries - Bride, Meaghan E.; Samarani, Francesca; Grant, Lauren E.; James, Fiona M. K. (Frontiers in Veterinary Science, 2024)
Epilepsy is a common neurological condition in dogs. Analysis of primary care populations across countries can provide a more complete understanding of the epidemiology of this condition and provide context for spectrum of care discussions. This narrative literature review was aimed at understanding canine epilepsy/seizure prevalence in primary care populations, and changes in occurrence across geography, culture, and socioeconomic status. There are few studies to give insight into the true general population of epileptic canines and there is inconsistency in the literature regarding the standards applied for epilepsy diagnosis across primary care and referral practices. Therefore, the future focus should be on more epidemiological research in primary care and mixed populations, more veterinary education to standardize use of medical guidelines in primary care settings, and increased awareness of the benefits of having pet insurance to mitigate the potentially substantial cost of care for dogs with epilepsy.